DIRECTION AND LEADERSHIP SITLES IN THE HUMAl" MANAGEMENT AREA: A CHARACTERIZATION PROCESS - Sánchez Manchola, Iván Darío (Cuadernos de Administración, 2007)
DIRECTION AND LEADERSHIP SITLES IN THE HUMAl" MANAGEMENT AREA: A CHARACTERIZATION PROCESS